Cities, Autonomy, and Decentralization in Japan - Carola Hein, Philippe Pelletier (Routledge, 2006)
Japan is known as a country in which a potent central power reigns over a compliant pyramidal hierarchy. For planning this has meant strong centralized government control. Yet, examples of autonomy have always existed in the politics, society, and economy of Japan and thrive today in various forms, particularly in urban areas. Following the growth and subsequent collapse of the bubble economy in 1990, and in response to globalization, new trends toward local autonomy and political and economic decentralization are emerging that must be evaluated in the context of the larger socio-political system. While the Tokyo megalopolis and other urban areas have been increasing in size and diversity of functions, both centralized authority and its expressions in planning are being questioned on various levels of Japanese government, among citizens, and in academia. At a time when Japan is ever more integrated into the global system, attempts at autonomy occur on the level of the neighborhood, the city, the region, and the island.